The Long Non-coding RNA MEG3/miR-let-7c-5p Axis Regulates Ethanol-Induced Hepatic Steatosis and Apoptosis by Targeting NLRC5 - Wang, Qin; Li, Mingfang; Shen, Zhiming; Bu, Fangtian; Yu, Haixia; Pan, Xueyin; Yang, Yang; Meng, Xiaoming; Huang, Cheng; Li, Jun (Frontiers in Pharmacology, 2018)
Ethanol (EtOH)-induced hepatic injury, characterized by hepatic steatosis with apoptosis, causes heavy health burden personally and socially. Long non-coding RNAs (lncRNAs) have been implicated in liver diseases. However, the role of lncRNA MEG3 in EtOH-induced hepatic injury remains unknown. The aim of present study was to assess the function of MEG3 and its functional interaction with miR-let-7c-5p in EtOH-induced hepatic injury. Here we observed that MEG3 and NLRC5 expression was increased and miR-let-7c-5p expression decreased in EtOH-fed mice and EtOH-induced AML-12 cells. Knockdown of MEG3 contributed to attenuation of EtOH-induced steatosis and apoptosis in AML-12 cells. Also, expression level of MEG3 negatively correlated with miR-let-7c-5p expression and positively correlated with NLRC5 expression. In contrary to MEG3, miR-let-7c-5p overexpression attenuated EtOH-induced steatosis and apoptosis, as well as suppressed EtOH-induced increase in NLRC5 expression. By luciferase reporter assay, we concluded that miR-let-7c-5p directly binds to NLRC5 3′-UTR, thereby negatively regulates NLRC5 expression. Our data suggested that lncRNA MEG3 functions as a competing endogenous RNA for miR-let-7c-5p to regulate NLRC5 expression in EtOH-induced hepatic injury.